Lithostratigraphy and evolution of the Lower Cretaceous Basins, in Western Saharan Atlas, Algeria. (March 2021) - Azil, Athmane; Ait Ouali, Rachid
Abstract: The Lower Cretaceous series in the Western Saharan Atlas are poorly dated, and they fill synclinal troughs on each side of the Jurassic anticlinal structures. These sequences vary between sectors and between flanks of a given anticline. The aim of the present study is to confirm whether the basins were independent of each other and isolated by Jurassic "islands". The field data show the importance of detritic deposits, particularly continental to nearshore red sandstones, which were deposited under tidal conditions, along with red and varicoloured clay units. These series can be subdivided into three lithostratigraphic mega sequence: Valanginian-Hauterivian, Barremian and Aptian-lower Albian. Large thickness variations are observed in most of the defined formations, especially the Valanginian-Hauterivian, at the regional and local scales on the flanks of the Jurassic anticline axes. The basal Lower Cretaceous formation, which is composed of sandstone interbedded with clay and limestone, filled the residual troughs in the paleo topography present at the end of the Jurassic. This basal formation contains rare benthic and planktic foraminifera that are present locally in the clay. However, these foraminifera do not provide a precise Valanginian-Hauterivian age. In the other formations, variations in thickness and facies are related to the different geodynamic histories of the depocenter. Moreover, the presence of numerous sliding structures confirms the relative tectonic activity of these basins, particularly during the Albian. The Aptian formation with a maximum thickness of 20 m, is constant in all studies zone. Highlights: Lithostratigraphic subdivisions of Lower Cretaceous Series based on sequence analysis. Sedimentological descriptions of Lower Cretaceous Series lead to definition of the depositional environments belong to the nearshore environment under the influence of wave or the tidal action. Correlations show significant variations in thickness and facies between flanks of tight Jurassic anticlinal structures suggesting the independence of the sub-basins. New biostratigraphic data suggests the various units that were hitherto, suggested to be Hauterivian unit are shown to be Barremian in age.